The presentation of gut microbiome-based personalized nutrition on the internet: simple and accessible, complex and inaccessible - Lee, Katharine; Davies, Russell G.; Barnett, Julie (Frontiers in Communication, 2023)
The gut microbiome is related to health and wellbeing, although the precise nature of the relationship and the involvement of and interaction with other factors is not fully understood. In this context, private companies are providing gut microbiome-based personalized nutrition services on the internet. Framed by social representation theory, we conducted an analysis of the websites of 27 companies offering direct-to-consumer personalized nutrition based on the microbiome, to understand how they communicate to prospective consumers. We found that through imagery, metaphor, and personification, companies simultaneously position the gut microbiome, and gut microbiome-based personalized nutrition, as both simple and accessible and complex and inaccessible. Highly medicalized content in the main web pages is negated in often peripheral disclaimer sections.